Development of Indicators on Automotive Technology Skills of Vocational Diploma Students: A Confirmatory Factor Analysis Model - Wuttichai Morjai; Phadungchai Pupat; Paitoon Pimdee (My University, 2018)
Abstract The present research was aimed to develop indicators on automotive technology skills and compare automotive technology skills of vocational diploma students among type of educational institutions. A stratified random sampling method was used to select a sample of 400 from the population of 1,337 second year vocational diploma students in Auto Mechanic Department under the Office of Vocational Education Commission in Samutprakan, Nonthaburi, Phathumthani, Saraburi, and Ayutthaya. The research instrument was a 5 rating scale questionnaire with a reliability of 0.956. The data analysis were first order a confirmatory factor analysis, mean, standard deviation, and one-way ANOVA. The findings were as followed. (1) The indicators on automotive technology skills of vocational diploma students comprised 20 indicators, is valid and fit to empirical data i.e. Chi-square = 98.314, df = 81, p = 0.093, GFI = 0.987, AGFI = 0.965, and RMSEA = 0.017. (2) The automotive technology skills of vocational diploma students among type of educational institutions were not different at a significance level of .05.
Keywords: Stratified Sampling; Mining Techniques and Economics